Enhancing Student Learning Outcomes in Narrative Writing Through the Use of Image Media - Marlius Lahagu (Jurnal Pendidikan Vokasi Indonesia, 2023)
Based on interviews conducted by the researcher with the class teacher, it was found that the students' narrative writing skills at MTs Al-Washiyah Pantai Labu did not meet the Minimum Competency Criteria (KKM) for the Indonesian Language subject, which is set at 65%. The students faced difficulties in storytelling. To address this issue, remedial actions were necessary. One potential solution for improving storytelling skills is the use of sequential images. This series of images is considered effective in motivating students to learn and stimulating them to generate writing ideas. The focus of this study is on improving students' narrative writing skills through the use of sequential image media. The aim of this research is to enhance the process and outcomes of narrative writing instruction for seventh-grade students at MTs Al-Washiyah Pantai Labu. This study uses a classroom action research (CAR) design, which was implemented over two cycles. The subjects of the study were the seventh-grade students of MTs Al-Washiyah Pantai Labu. Data collection in each cycle employed both test and non-test techniques. The test used was an essay test, while the non-test techniques involved observing student learning activities, the use of sequential image media, and teacher activities. Data analysis was conducted using both quantitative and qualitative techniques.